Disaster and political trust: A natural experiment from the 2017 Mexico City earthquake - Margaret Frost; Sangeun Kim; Carlos G. Scartascini; Paula Zamora; Elizabeth J. Zechmeister (Inter-American Development Bank (IDB), 2024)
Political trust is foundational to democratic legitimacy, representative governance, and the provision of effective public policy. Various shocks can influence this trust, steering countries onto positive or negative trajectories. This study examines whether natural disasters can impact general political trust and if disaster relief efforts can mitigate these effects. We investigate the relationships between disaster, trust, and aid using novel survey data collected before and after a 7.1-magnitude earthquake struck Mexico City in September 2017. Our findings reveal that the disaster resulted in an 11% decrease in general political trust. Additionally, we demonstrate that geographical proximity to disaster relief efforts may counterbalance this decline in trust. This study contributes to the scholarship on the politics of disasters and offers policy implications, highlighting the role of disaster assistance in potentially restoring general political trust after a disaster.
Keywords: H84; Q54; D72; Z13; 330; Political trust; Natural disaster; Natural experiment; Aid relief; Development